The diagnosis and management of agitation - Nordstrom, Kimberly; Wilson, Michael P. 1969-; Zeller, Scott L. (Cambridge University Press, 2017)
A common symptom of psychiatric and medical disorders, agitation often appears in a variety of medical environments. This practical guide explores the origins of the condition and the differing approaches and treatments available. The biology of agitation is discussed, followed by specific chapters on substance abuse, medical causes, personality disorders, and treatment in pediatrics and the elderly. Treatment options including psychiatric work-ups, medical work-ups, psychopharmacology, de-escalation, and calming techniques are provided. The complexities of legal issues, patients' rights, and prehospital settings are also addressed, providing physicians, nurses, and mental health workers with a comprehensive resource in providing safe, focused, and effective treatment.